ANALISIS KARAKTER ASMA, NURDIN, DAN RIDHWAN DALAM NOVEL MELALUI JALAN RAYA DUNIA KARYA A. HASJMY - Nursimah - (Mentari: Majalah Ilmiah Universitas Muhammadiyah Aceh, 2013)
The research is aim to describe the behavior aspect of figures in the novel Melalui Jalan Raya Dunia work of A. Hasjmy. The data source of this research is novel Melalui Jalan Raya Dunia work of A. Hasjmy which edited by BulanBintang first edition 1978. The data collection conducted by documentation technique. Data analyzed by use qualintative. The result of research indicated that the behavior of three figures in novel Melalui Jalan Raya Duniawere correspond to dimension of psychology. The main three figures in that novel are Asma, Nurdin, and Ridhwan. The analysis result indicated that (1) at first, Asma have kind, polite, lover, and kind heart behaviors. Result has a household conflict, her behavior become different. He has a chronic frustration. (2) at first, has kind, polite, lover, friendly, and discipline behaviors. Result has a household conflict his behavior become different. He has frustration. (3) Ridhwan has polite, kind and wise, lover, discipline, well-educated, and patient behaviors. Result ofoccurring the household conflict his behavior become different close to frustration behavior, such as stolid and sentimentalist. But, because he can make adaptation, finally he becomes successful, especially in education. The behaviors that in form of frustration are: sublimation, projection, rationalization, repression, apathetic, aggressive, react to clear the track, stereotype, judge forhimself, and sadness. The behaviors have adaptation form are: transfer, regression, reaction of formation, have imagine, cover to debility, self-improvement, motivation, love, and abashment.Â Key words: analysis, aspect, attitude, figure, novelÂ